Gonorrhoea in Greenland, incidence and previous preventive measures: a review to improve future strategies. Issue 1 (1st January 2017) - Berntsen, Sine; Karlsen, Anders Peder Højer; Pedersen, Michael Lynge; Mulvad, Gert
ABSTRACT: Gonorrhoea continues to be a significant health challenge in Greenland. The aim of this study was to describe the development of gonorrhoea in Greenland through time including incidence rates and previous measures taken to address the challenge. A systematic literature search in PubMed, Embase and The Cochrane Library was conducted. Furthermore, local archives were searched in the Health Clinic in Nuuk for relevant literature. From the 1940s the incidence of gonorrhoea increased steadily with a steep incline around 1970, possibly as a consequence of changes in living conditions and urbanisation. Significant declines in the incidence were seen the late 1970s and again in the late 1980s, most likely in the wake of an outbreak of ulcus molle/chancroid in the 1970s and as a result of focused education in venereology for Greenlandic nurses in the late 1980s combined with the stop-AIDS campaign. Since the early 1990s the incidence of gonorrhoea in Greenland has not risen to previously high levels. However, the incidence remains high and with a gradually increasing trend. Prevention intervention strategies such as peer-to-peer sexual education, storytelling and involvement of parent/guardian in sexual education of the youth could be appropriate approaches to improve sexual health in Greenland.